Effect of Nitrogen Supplementation additives at Casing on the Productivity and Quality of the mushroom Agaricus bisporus - Abdullah A. Hassan; Karkaz M. Thalij; Jamal J. Ahmad (Tikrit Journal of Pure Science)
This study aims to assay the effect of the separate supplementation with 1, 3 and 5% of (Erbil Feed, WAFI HOLAND, Lysine, Methionine, Ammonium Chloride and Calcium Nitrate) at casing on the productivity and quality of the mushroom Agaricus bisporus. Results indicated a significant increase in total production and biological efficiency. with treatment of 1% Erbil Feed. When total production increased from 21.68 kg / m2 in the control to 23.20 kg / m2 with this supplement. While the biological efficiency was increased from 72.26% to 77.33% with the same supplement. Treatment 1% of Erbil Feed was also recorded earliest production reached at 16 days after casing than controls at 18 days. The qualitative traits of 3% Methionine has recorded higher of total antioxidants contents at 1975 µg/ g dry weight comparison with control, which was 1572 µg/ g dry weight, as well as recording the 3% of Erbil Feed gave a higher protein contents 36.85% compared to the control treatment  22.36 %.